(untitled) (Clinics, 2013)
OBJECTIVES: Administering steroids before cardiopulmonary bypass in pediatric heart surgery modulates systemic inflammatory response syndrome and improves postoperative recovery. However, the use of steroids aggravates hyperglycemia, which is associated with a poor prognosis. Adult patients with systemic inflammatory response syndrome usually evolve with hyperglycemia and high insulin levels, whereas >;90% of pediatric patients exhibit hyperglycemia and low insulin levels. This study aims to determine: A) the metabolic and inflammatory factors that are associated with hyperglycemia and low insulin levels in children who underwent cardiac surgery with cardiopulmonary bypass and who received a single high dose of methylprednisolone and B) the best predictors of insulin variation using a mathematical model. METHODS: This preliminary study recruited 20 children who underwent heart surgery with cardiopulmonary bypass and received methylprednisolone (30 mg/kg) immediately after anesthesia. Among the 20 patients initially recruited, one was excluded because of the absence of hyperglycemia and lower insulin levels after surgery. However, these abnormalities were confirmed in the remaining 19 children. The C-peptide, CRP, IL-6, and adrenomedullin levels were measured before surgery, immediately after cardiopulmonary bypass, and on the first, second, and third days after cardiac surgery. RESULTS: IL-6, CRP, and adrenomedullin increments were observed, whereas the C-peptide levels remained within reference intervals. CONCLUSION: The multiple regression model demonstrated that in addition to age and glycemia (two well-known factors that are directly involved in glucose metabolism), adrenomedullin and IL-6 levels were independent factors associated with lower insulin concentrations. These four parameters were responsible for 64.7% of the observed insulin variances. In addition, the fact that C-peptide levels did not fall together with insulin could have grounded the medical decision not to administer insulin to patients.